الدوریات المصریة فى قواعد بیانات الاستشهادات المرجعیة العالمیة : دراسة تحلیلیة - د. سهیر عبد الباسط عید (المجلة الدولية لعلوم المكتبات والمعلومات)
The registration of refereed scientific journals in global databases isone of the standards used to classify universities as well as countries; somany different countries seek to add their scientific journals in globaldatabases. The current study is trying to identify Scopus’s coverage ofjournals, particularly the Egyptian journals, and analyze the characteristicsof the references cited in these journals. Thus finding out where the ArabRepublic of Egypt stands on the map of international publication bydetermining the number of Egyptian journals indexed in Scopus. Based onthe bibliographic measurements method (Bibliometric), and citationsanalysis, the study came out with a set of findings and recommendations,which may help knowing the best ways of indexing a number of otherEgyptian journals in global database.